Pengembangan Sumber Daya Pendidikan pada Generasi Milenial Melalui Era 5.0 dan Local Genius 6.0 - R. Madhakomala; Eliana Sari; Muhamad Fadholi; Satri Dwi Kurnia Nasution; Hazrat Shah Kayen (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2024)
This research examines the development of educational resources in the millennial generation era by utilizing the Society 5.0 and Local Genius 6.0 approaches. The main focus of this research is how these two concepts can be applied in developing an educational curriculum that is more adaptive, relevant to modern technology, and still maintains local values. Using an explorative method, this research found that the merging of technology and local wisdom resulted in significant improvements in education quality, student engagement, as well as strengthening cultural identity. Despite some obstacles such as gaps in access to technology and limited resources, the results show that this holistic approach is effective in improving the quality of education in the digital era.